Transcriptome Architecture of Osteoblastic Cells Infected With Staphylococcus aureus Reveals Strong Inflammatory Responses and Signatures of Metabolic and Epigenetic Dysregulation - Nicolas, Aurélie; Deplanche, Martine; Commere, Pierre-Henri; Diot, Alan; Genthon, Clemence; Marques da Silva, Wanderson; Azevedo, Vasco; Germon, Pierre; Jamme, Hélène; Guédon, Eric; Le Loir, Yves; Laurent, Fréderic; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococcus aureus is an opportunistic pathogen that causes a range of devastating diseases including chronic osteomyelitis, which partially relies on the internalization and persistence of S. aureus in osteoblasts. The identification of the mechanisms of the osteoblast response to intracellular S. aureus is thus crucial to improve the knowledge of this infectious pathology. Here we present an in-depth analysis of the effect of long-term S. aureus infection on the transcriptional program of human osteoblast-like cells. We developed a novel model of long-term S. aureus infection, with a selection of solely bacteria-bearing osteoblast-like cells by flow cytometry, to identify signals specific to intracellular infection. After RNA-seq and KEGG and Reactome pathway enrichment analysis, the remodeled transcriptomic profile of infected cells revealed exacerbated immune and inflammatory responses, as well as metabolic dysregulations that likely influence the intracellular life of bacteria. Numerous genes encoding epigenetic regulators were downregulated. The later included genes coding for components of chromatin-repressive complexes (e.g., NuRD, BAHD1 and PRC1) and epifactors involved in DNA methylation. Sets of genes encoding proteins of cell adhesion or neurotransmission were also deregulated. Our results suggest that intracellular S. aureus infection has a long-term impact on the genome and epigenome of host cells, which may exert patho-physiological dysfunctions beyond the infection process. Overall, these results not only improve our conceptual understanding of biological processes involved in the long-term S. aureus infections of osteoblast-like cells, but also provide an atlas of deregulated host genes and biological pathways and identify novel markers and potential candidates for prophylactic and therapeutic approaches.